An EEG index of sensorimotor interhemispheric coupling after unilateral stroke: clinical and neurophysiological study. (11th January 2018) - Pichiorri, Floriana; Petti, Manuela; Caschera, Stefano; Astolfi, Laura; Cincotti, Febo; Mattia, Donatella
Abstract: Brain connectivity has been employed to investigate on post‐stroke recovery mechanisms and assess the effect of specific rehabilitation interventions. Changes in interhemispheric coupling after stroke have been related to the extent of damage in the corticospinal tract (CST) and thus, to motor impairment. In this study, we aimed at defining an index of interhemispheric connectivity derived from electroencephalography (EEG), correlated with CST integrity and clinical impairment. Thirty sub‐acute stroke patients underwent clinical and neurophysiological evaluation: CST integrity was assessed by Transcranial Magnetic Stimulation and high‐density EEG was recorded at rest. Connectivity was assessed by means of Partial Directed Coherence and the normalized Inter‐Hemispheric Strength (nIHS) was calculated for each patient and frequency band on the whole network and in three sub‐networks relative to the frontal, central (sensorimotor) and occipital areas. Interhemipheric coupling as expressed by nIHS on the whole network was significantly higher in patients with preserved CST integrity in beta and gamma bands. The same index estimated for the three sub‐networks showed significant differences only in the sensorimotor area in lower beta, with higher values in patients with preserved CST integrity. The sensorimotor lower beta nIHS showed a significant positive correlation with clinical impairment. We propose an EEG‐based connectivity index which is a measure of the interhemispheric cross‐talking and correlates with functional motor impairment in subacute stroke patients. Such index could be employed to evaluate the effects of training aimed at re‐establishing interhemispheric balance and eventually drive the design of future connectivity‐driven rehabilitation interventions. Abstract : We defined an EEG index of interhemispheric connectivity (nIHS) correlated with Corticospinal Tract (CST) integrity (assessed with TMS) and clinical impairment after stroke. The nIHS index in lower beta on the sensorimotor area was higher in patients with preserved CST and positively correlated with motor impairment expressed by the Fugl‐Meyer Assessment (FMA). Our index could be employed to evaluate the effects of rehabilitation aimed at re‐establishing interhemispheric balance after stroke.